Suppose f(x) = 6(6x - 5) + 6. Solve f(x) = 0 for x.

3 answers

6 (6x-5) + 6 = 0
6x - 5 = -1
6 x = 4
x = 2/3
===========
check
===========
6 (6*2/3 -5) + 6 = 0 ?
6 (4-5) + 6 = 0 ?
6 (-1) + 6 = 0 sure enough
Thank you both
Similar Questions
  1. I cannot solve the problem please help me.I'm suppose to set the equations up to solve for t. x = y + rt + at^2/2 Even when I
    1. answers icon 1 answer
  2. Solve:sec(x)^2= 3tanx +1 *** It is suppose to be the sqaure root of 3 but i could find the symbol so just wrote the 3 without it
    1. answers icon 1 answer
    1. answers icon 10 answers
    1. answers icon 1 answer
more similar questions